Loanwords from unattested Nordic source forms in Saami - Aikio, Ante (Finnisch-Ugrische Forschungen, 2020)
Among the numerous loanwords Saami has adopted from Proto-Norse there are also cases where the loan original has not been retained in modern or historically attested Nordic languages. Such etymologies can nevertheless be established on the basis of surviving cognate forms in other Germanic languages. Seven previously proposed etymologies of this kind are scrutinized, including those for North Saami duodji ‘handicraft’ and ráidalas ‘ladder’. Twelve new etymologies of the same type are argued for, among them explanations for the origin of North Saami ámadadju ‘face’, iktit ‘reveal, disclose’, and ivdni ‘color’.